Clinically significant pseudophakic cystoid macular edema after bag-in-the-lens implantation. Issue 4 (April 2020) - Scheers, Dorothée; Van Os, Luc; Ní Dhubhghaill, Sorcha; Wouters, Kristien; Tassignon, Marie-José
Abstract : This study shows that the BIL IOL implantation technique shows a comparable incidence of clinically significant PME to the standard implantation technique despite using a primary posterior continuous curvilinear capsulorhexis. Abstract : Purpose: To determine the incidence of clinically significant pseudophakic cystoid macular edema (CSPME) after phacoemulsification using the bag-in-the-lens intraocular lens (BIL IOL) implantation technique and to examine the influence of associated risk factors, both ocular and systemic. Setting: Monocentric, Antwerp University Hospital, Belgium. Design: Retrospective. Methods: This study included 1 077 first-operated eyes of 1 077 adults who underwent phaco-emulsification cataract surgery using the BIL IOL implantation technique between January 2013 and December 2015. Results: The 3-month incidence of CSPME in the subgroup without risk factors was 0% (95% CI, 0.0-0.0). The 3-month incidence of CSPME in the subgroup with risk factors was 2.8% (95% CI, 1.3-4.3). The 3-month incidence of CSPME in the total group of 1077 patients was 1.4% (95% CI, 0.6-2.1). The risk factors most significantly associated with CSPME included diabetes (hazard ratio [HR]: 5.37; 95% CI, 1.5-19.3; P = .019), exudative age-related macular degeneration (HR: 121; 95% CI, 36.1-409; P < .001), and macular traction (HR: 6.47; 95% CI, 1.9-22.1; P < .009). Conclusions: The incidence of CSPME was zero in eyes without risk factors. The incidence was consistent with previous reports in the literature regarding the lens-in-the-bag IOL implantation technique in eyes with risk factors. This indicates that the BIL IOL implantation technique is a safe procedure and does not confer a higher risk for developing cystoid macular edema after cataract surgery compared with the lens-in-the-bag IOL implantation technique, despite the requirement of a primary posterior continuous curvilinear capsulorhexis.